Top-down nanofabrication and characterization of 20 nm silicon nanowires for biosensing applications - Md Nor, Mohammad Nuzaihan; Hashim, Uda; Md Arshad, Mohd Khairuddin; A. Rahim, Ruslinda; Rahman, S. F. A.; Mohamad Fathil, Mohamad Faris; Ismail, Mohd. H. (Public Library of Science, 2016)
A top-down nanofabrication approach is used to develop silicon nanowires from silicon-oninsulator (SOI) wafers and involves direct-write electron beam lithography (EBL), inductively coupled plasma-reactive ion etching (ICP-RIE) and a size reduction process. To achieve nanometer scale size, the crucial factors contributing to the EBL and size reduction processes are highlighted. The resulting silicon nanowires, which are 20 nm in width and 30 nm in height (with a triangular shape) and have a straight structure over the length of 400 μm, are fabricated precisely at the designed location on the device. The device is applied in biomolecule detection based on the changes in drain current (Ids), electrical resistance and conductance of the silicon nanowires upon hybridization to complementary target deoxyribonucleic acid (DNA). In this context, the scaled-down device exhibited superior performances in terms of good specificity and high sensitivity, with a limit of detection (LOD) of 10 fM, enables for efficient label-free, direct and higher-accuracy DNA molecules detection. Thus, this silicon nanowire can be used as an improved transducer and serves as novel biosensor for future biomedical diagnostic applications.